Ticagrelor Use in Acute Myocardial Infarction: Insights From the National Cardiovascular Data Registry - Basra, Sukhdeep S. (J Am Heart Assoc, 2018)
BACKGROUND: Ticagrelor is a P2Y(12) receptor inhibitor with superior clinical efficacy compared with clopidogrel. However, it is associated with reduced efficacy when combined with a high‐dose aspirin. METHODS AND RESULTS: Patients in the acute coronary treatment and intervention outcomes network (ACTION) Registry‐Get With The Guidelines (GWTG) with acute myocardial infarction from October 2013 through December 2014 were included in the study (167 455 patients; 622 sites). We evaluated temporal trends in the prescription of P2Y(12) inhibitors, and identified factors associated with ticagrelor use at discharge. Among patients discharged on ticagrelor and aspirin (21 262 patients), we evaluated the temporal trends and independent factors associated with high‐dose aspirin prescription at discharge. Ticagrelor prescription at discharge increased significantly from 12% to 16.7% (P<0.0001). Decreases in prasugrel and clopidogrel use at discharge (15.7%–13.9% and 54.2%–51.1%, respectively, P<0.0001) were also observed. Independent factors associated with preferential ticagrelor prescription at discharge over clopidogrel included younger age, white race, home ticagrelor use, invasive management, and in‐hospital re‐infarction and stroke (P<0.0001 for all), whereas older age, female sex, prior stroke, home ticagrelor use, and in‐hospital stroke (P<0.0001 for all) were associated with preferential ticagrelor prescription at discharge over prasugrel. High‐dose aspirin was used in 3.1% of patients discharged on ticagrelor. Independent factors associated with high‐dose aspirin prescription at discharge included home aspirin use, diabetes mellitus, previous myocardial infarction, previous coronary artery bypass graft, ST‐segment–elevation myocardial infarction, cardiogenic shock, and geographic region (P=0.01). CONCLUSIONS: Our contemporary analysis shows a modest but significant increase in the use of ticagrelor and a high rate of adherence to the use of low‐dose aspirin at discharge.